Water table response to a pumping test in the hinterland core area of the Taklimakan Desert, China - Yaping, Wei; Jinglong, Fan; Xinwen, Xu; Jiaqiang, Lei (Tecnología y ciencias del agua, 2017)
Wei, Y., Fan, J., Xu, X., & Lei, J. (March-April, 2017). Water table response to a pumping test in the hinterland core area of the Taklimakan Desert, China. Water Technology and Sciences (in Spanish), 8(2), 151-158.In this article, hydrogeological parameters were determined by a single well pumping test. Over the course of the study, BETCO was used to eliminate the effects of atmospheric pressure changes on water level based on the regression deconvolution method. The aquifer test was used to analyze data and to calculate hydrogeological parameters. Finally, from the three unconfined aquifer models, though the Boulton model cannot successfully gain well-fitting results, the Theis model with Jacob correction and the Neuman model results obtained hydrogeological parameters by curve-fitting. Additionally, permeability coefficient of the two models is in good agreement with previous research, which can provide a reference for further study in the hinterland of the desert, especially for the construction of hydrological modeling research.